BENCANA GEOLOGI DAN EVALUASI PENGEMBANGAN INFRASTRUKTUR WILAYAH PESISI,R TELUK RAJEGWESI, BANYUWANGI - E. Usman (Jurnal Geologi dan Sumberdaya Mineral, 2008)
Geologically, the area of Rajegwesi Bay is potential for geological hazard (earthquake and tsunami). The area of Rajegwesi Bay is located in the front of the Jawa Trench which has high risk in seismicity. In 1994, the south coast of Banyu.wangi was attacked by an earthquake and tsunami where the wave had reached more than 10m high. The huge damage happened on bays where many peoples lives including Rajegwesi Bay. The coastal characteristic mapping shows the coastal plain lies less than 4 m and it represents the area that has a high wave and longshore current. The settlement on Rajegwesi Bay is located in coastal plain area, and when a tsunami happens, it will be sweeped by waves. Based on seismicity aspects in this area, the intrsstructug: locations determined by the local government of Banyuwangi must be revised and removed to safe locations, i.e, the area which lies more than 10m above sea level. Keywords: earthquake, tsunami, settlement, Rajegwesi Bay